The impact of some knowledge sharing factors in achieving competitive advantage An Analytical study of the views of sample choosing from some faculty staff of Salahadin University / Erbil - ىٍدرس اىٍصاغد شٍ٘رة غيٖ اةراًْ٘ (QALAAI ZANIST JOURNAL, 2021)
This research focuses on two main variables: Factors of knowledge sharing which its dimensions are (knowledge sharing, team work, staff training, collaborative environment), and the second variable is competitive advantage with the dimensions of (quality, creativity, cost, flexibility). The main aims of this research are to provide conceptual framework for the variables and try to test the University of Salahadin as a field of application. A questionnaire was distributed to a sample of faculty members at Salahadin University, 145 forms were distributed to the faculty members, 136 were retrieved and 132 were valid. Two main hypotheses emerged, in order to analysis the data statistic software called SPSS was used to test the hypotheses that were developed and to address the research problem. The research reached a number of conclusions, which the main once were the existences of significant correlation and influence between the two variables of Knowledge sharing and competitive advantage where the research results indicates the importance of the role of knowledge sharing factors in achieving competitive advantage. Finally, based on the research results, the research presented several recommendations, the most important of which were the need for universities to study the factors of knowledge sharing, especially those related to the training of workers and team work, which has a positive impact on knowledge sharing and thus a reflection on enhancing competitive advantage. Also the research recommended that university should provide financial support and facilities especially in the area of participation in conferences, seminars and training courses.